1997
DOI: 10.1148/radiology.205.1.9314986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 14- and 11-gauge directional, vacuum-assisted biopsy probes and 14-gauge biopsy guns in a breast parenchymal model.

Abstract: Statistically significant differences with various biopsy devices are seen in the breast tissue yield and in fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 0 publications
2
49
0
2
Order By: Relevance
“…Mean specimen weights of 94 mg for the former versus less than 18 mg for the latter have been reported [7]. This increase in tis with published results [5,6].…”
Section: Discussionsupporting
confidence: 83%
“…Mean specimen weights of 94 mg for the former versus less than 18 mg for the latter have been reported [7]. This increase in tis with published results [5,6].…”
Section: Discussionsupporting
confidence: 83%
“…Sim et al (17) reported that the underestimation rate of DCIS (26%) was significantly higher when preoperative biopsies were performed using core biopsy needles, compared with the lower underestimation rate of DCIS (19.9%) in biopsies obtained using VAB devices. Although SVAB allows more accurate histopathologic results, underestimation still occurs (7,10,18). Some investigators have found rates of underestimation ranging from 5% to 29% for DCIS at SVAB (6,9,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Large core SVAB allows larger samples to be obtained in a shorter period of time compared with samples obtained using automated core biopsy devices (7). Moreover, this technique has the advantage of a single insertion in the area of interest compared with automated core biopsy…”
mentioning
confidence: 99%
“…The rate of underestimation of ADH has been reported to range from 11% to 65% for 14-gauge automated biopsy (14)(15)(16)(17)(18)(19)(20). Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis. Despite these improvements, the rate of underestimation for ADH has been reported as 10% to 26% for 11-gauge vacuum-assisted biopsy (VAB) (2,14,(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%